Optimising a co-production framework for developing public health interventions: application and testing of school-based Research Action Groups - Hayley Reed; Simon Murphy; Rhiannon Evans (Health Research Policy and Systems, 2023)
Abstract Existing frameworks for developing public health interventions have limited guidance for researchers on how to work with stakeholders to co-produce context-specific interventions. To address this, a promising framework for the co-production of public health interventions was developed through a previous review of school-based co-production. The present study aimed to optimise this co-production framework through applying and testing it in real-world secondary school contexts. Within schools, Research Action Groups (RAGs) were established with multiple school stakeholders supported by an external facilitator to use school data to produce school-specific mental health and wellbeing interventions. A mixed method process evaluation of two contextually diverse case study secondary schools in the UK was used to optimise the co-production framework. The process evaluation sought the views of those involved (students, school staff, school Senior Management Team (SMT) members, and the external co-production facilitator/researcher) on the co-production functions they were involved in so they could be modified, if needed. Data collected for the process evaluation during co-production were a researcher diary (n = 45 entries), and observations of student photography (n = 21) and RAG meetings (n = 8). Post co-production, interviews, and surveys with RAG students (n = 18) and staff (n = 8), and two school-specific SMT focus groups (n = 10) were conducted. The study identified four recommendations to optimise and integrate co-production into real world practice. They include the need to: assess schools for their readiness to undertake co-production; more effectively communicate the necessity to have stakeholders from the whole system involved; work with SMTs throughout co-production functions; involve stakeholders outside the school to support producing solutions to change school mental health and wellbeing priorities. The framework is intended to be used by researchers to integrate stakeholders into a shared decision-making process to develop interventions that meet the needs and contexts of individual schools. It could be transferred to other settings to support the development of public health interventions for other health areas, and populations. Further evaluation to test its use in other settings is needed.